PROTEIN FIMBRIA 16 kDa BAKTERI ACINETOBACTER BAUMANNIIDARI URIN PENDERITA INFEKSI SALURAN KEMIH BERPERAN SEBAGAI PROTEIN HEMAGLUTININ DAN ADHESIN - Noorhamdani, Noorhamdani (Jurnal Kedokteran Brawijaya, 2005)
Acinetobacter baumannii (Acb) is an opportunistic and nosocomial pathogen that ussualy found in clinical specimen from patients with intensive care. The pathogenic mechanism of this bacteria are not fully elucidated especially potential activity of its protein as hemaglutinin and adhesion molecul. The aim of this study is to evaluate the  role of 16 kDa fimbriae protein from urnary tract infection (UTI) patient as hemaglutinin and adhesion molecule. Usingexplorative design this study was started by isolation Acb bacteria from urine of patient that had been determine as UTI clinically and laboratory. After identification this bacteria by microbact system hemaglutination test and isolation  of its fimbriae fraction, 12.5% SDS-PAGE had been used to isolated fimbriae protein, following assay in vitro to adhesion test..The study showed that the 16 kDa fimbriae protein of Acb bacteria was a hemaglutinin protein that could agglutinate 0.5% mice erythrocytes (1/32), and human blood group O erythrocytes (1/8). Hemaglutination test were negative onerythrocytes from rat, guinea pig, sheep, and human blood group A, B. The 16 kDa fimbriae protein (AF16) was also adhesion protein that had been revealed by its activity to adherenceto receptor of mice enterocytes. The increasing dose of AF16 molecules will decrease the amount of Acb bacteria to adherence to enterocytes (p<0.05). The fimbriae of Acb is maybe classified P type. Key words:Acinetobacter baumannii, fimbriae, hemaglutinin protein, adhesion protein